Several potentiality enhancement techniques of water flooding reservoir in placanticline - Zhang Yichi (E3S Web of Conferences, 2022)
The three types of oil reservoirs in water drive have entered the later stage of ultra-high water cut development [1] after three times of well pattern infilling adjustment and years of oil stabilization and water control. With the gradual transfer of high quality reserves to chemical flooding, the development objects of water flooding are mainly three types of oil reservoirs, and the exploitation objects are getting worse and worse, and the difficulty of controlling decline, exploiting potential and benefit development is increasing year by year. To this end, the blocks that have been tested for water control and efficiency improvement are selected to conduct precise potential-tapping tests, to carry out technological breakthroughs of “water control and efficiency improvement”, to explore and form a series of high-efficiency development technologies of water flooding, and to guide the deep potential-tapping in the ultra-high water-cut stage of water flooding [2]. This paper mainly focuses on the comprehensive utilization of injection and production well pattern, as well as the principle and effect of injection well comprehensive adjustment program and tracking adjustment program.